Generation of a human induced pluripotent stem cell line (UNIFEi001-A) from a patient with Spinocerebellar ataxia type 1 (SCA1) - Mariangela Pappadà; Sara Melija; Martina Facchini; Mara Martino; Sofia Minarini; Anna Caproni; Chiara Nordi; Paola Rimessi; Rita Selvatici; Peggy Marconi (Stem Cell Research)
Spinocerebellar ataxia type 1 (SCA1) is one of six SCAs related to the expansion of a CAG repeat, encoding glutamine. Induced pluripotent stem cells were generated by reprogramming fibroblasts isolated from a patient affected by SCA1, through the transduction of three viral vectors derived from a non-integrative virus. UNIFEi001-A cell line presents an ESC-like morphology, is vector-free, expresses pluripotency markers, presents a normal karyotype and can differentiate into the three germ layers. These cells can be further differentiated into neural stem cells and neurons to serve as a cellular model.